2017
DOI: 10.1021/acs.orglett.7b01795
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to 3-(Indol-2-yl)succinimide Derivatives by Manganese-Catalyzed C–H Activation

Abstract: The manganese-catalyzed addition of C-2 position of indoles to maleimides has been achieved under additive-free conditions. The manganese catalyst exhibits excellent chemo- and regioselectivity, good functional group compatibility, and high catalytic efficiency. The substrate scope can also be extended to maleates, ethyl acrylate, 1,4-dihydro-1,4-epoxynaphthalene, pyrroles, and 2-phenylpyridine, which further demonstrates the universality of this straightforward approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(43 citation statements)
references
References 75 publications
0
40
0
1
Order By: Relevance
“…Although the C2-alkylation of N-(2-pyri(mi)dyl)indoles with alkenes can be catalyzed by ar ange of metals including ruthenium, [162] cobalt, [168c, 192] manganese, [193] and rhodium, [194] Ackermannss electivity-switchable,c obalt-catalyzed alkylation [192b] is probably the most versatile method reported to date (Scheme 40). Te rminal unactived alkenes could indeed be used for the C2-alkylation of N-(2-pyridyl)indoles with catalytic amounts of Cp*Co(CO)I 2 and AgSbF 6 ,w ithout or with 1-adamantylcarboxylic acid to provide linear or branched products,respectively.Detailed mechanistic studies revealed ac hange in the mechanism from al inear-selective ligand-to-ligand hydrogen transfer to ab ranched-selective carboxylate-assisted internal electrophilic-type substitution in the presence of the carboxylate additive.A ne specially efficient and appealing enantioselective version based on the use of ac hiral carboxylic acid was moreover reported recently.…”
Section: Alkylation With Alkenesmentioning
confidence: 99%
“…Although the C2-alkylation of N-(2-pyri(mi)dyl)indoles with alkenes can be catalyzed by ar ange of metals including ruthenium, [162] cobalt, [168c, 192] manganese, [193] and rhodium, [194] Ackermannss electivity-switchable,c obalt-catalyzed alkylation [192b] is probably the most versatile method reported to date (Scheme 40). Te rminal unactived alkenes could indeed be used for the C2-alkylation of N-(2-pyridyl)indoles with catalytic amounts of Cp*Co(CO)I 2 and AgSbF 6 ,w ithout or with 1-adamantylcarboxylic acid to provide linear or branched products,respectively.Detailed mechanistic studies revealed ac hange in the mechanism from al inear-selective ligand-to-ligand hydrogen transfer to ab ranched-selective carboxylate-assisted internal electrophilic-type substitution in the presence of the carboxylate additive.A ne specially efficient and appealing enantioselective version based on the use of ac hiral carboxylic acid was moreover reported recently.…”
Section: Alkylation With Alkenesmentioning
confidence: 99%
“…This type of addition reaction has been successfully extended with manganese catalyst by Song and his co‐workers. When N ‐pyridylindole ( 12 a ) was treated with N ‐phenylmaleimide ( 13 a ) in the presence of Mn 2 (CO) 10 (10 mol%) at 120 °C in EtOAc, a C‐2 alkylated indole derivative 14 a was observed in 90% yield (Scheme ) . Interestingly, the neutral manganese complex effectively catalyzed the reaction under air atmosphere.…”
Section: Ortho Alkylation Of Aromatics With Maleimidesmentioning
confidence: 99%
“…Die C2-Alkylierung von N-(2-Pyri(mi)dyl)indolen mit Alkenen kann von diversen Metallen katalysiert werden, einschließlich Ruthenium, [162] Cobalt, [168c, 192] Mangan [193] und Schema 39. Palladium-und rhodiumkatalysierte ortho-Alkylierung von 2-(N-Heteroaryl)arenen mit Alkylborreagentien.…”
Section: Alkylierung Mit Alkenenunclassified